Soil stabilizer with pore self-sealing function and preparation method thereof
By introducing sodium metaaluminate, nanosilicon dioxide, sodium silicate, gypsum, calcium chloride and self-sealing functional microcapsules into the soil curing agent, the problem of poor water resistance of magnesium oxychloride-based gelling materials is solved, and high Cured soil with strength and water stability is suitable for road base soil and has the advantages of low energy consumption and low carbon emissions.
Patent Information
- Application Number
- CN202411359265.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-14
AI Technical Summary
Magnesium oxychloride-based gelling materials have poor water resistance during soil curing, resulting in a decrease in the strength of the cured soil, limiting their application in road engineering.
Soil curing agent containing sodium metaaluminate, nanosilicon dioxide, sodium silicate, gypsum, calcium chloride, polyanionic cellulose and self-sealing functional microcapsules are used, and the microcapsules are insoluble under alkaline conditions. urea and urease are dissolved and released under sexual conditions to generate expanded reaction products to enclose pore channels, thereby improving the water stability and strength of the solidified soil.
It significantly improves the water stability and durability of magnesium oxychloride-based gelling materials. The unlimited compressive strength of 7d can reach more than 3MPa, and the water stability coefficient reaches more than 100%, meeting the demand for road base soil solidification, while reducing the Energy consumption and carbon emissions in the production process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of road engineering construction, and in particular to a soil solidifying agent with pore self-sealing function and a preparation method thereof. Background Art
[0002] Waste-free city construction is of great significance to environmental protection and reducing the consumption of natural resources. In the process of urban construction, a large amount of engineering waste soil will inevitably appear. How to deal with this engineering waste soil is a major challenge facing waste-free city construction. Soil solidification and resource utilization is an effective way to solve this problem and is receiving increasing attention.
[0003] Cement and lime are still the most widely used soil stabilization materials, but the production process of cement and lime has the disadvantages of high energy consumption and high carbon emissions, which is contrary to the concept of zero-waste cities. In addition, when lime and cement are used as solidification materials, the solidified soil also has the limitations of easy cracking and poor water stability.
[0004] The calcination temperature of magnesium oxychloride cement is low during production, and it does not involve the calcination of limestone. Therefore, magnesium oxychloride cement has the advantages of low energy consumption and low carbon emissions. In addition, magnesium oxychloride cement can also be produced using some industrial by-products and waste materials. Therefore, magnesium oxychloride cement is a relatively environmentally friendly and green cementitious material. However, the hydration product of magnesium oxychloride cement has poor phase stability in a humid environment. Therefore, there are still great challenges in using magnesium oxychloride cement as a soil solidification material.
[0005] Patent CN 109305794 A discloses a magnesium oxysulfide-based raw soil curing agent, a preparation method and an application thereof. The main components of the curing agent are light-burned magnesium oxide powder, magnesium sulfate solution, toughened anti-cracking fiber, reinforcing additive and water-resistant additive. However, the minimum curing agent dosage in this method reaches 140%, which is too high. In addition, the water stability coefficient of the sample after immersion in water is 0.81, and the water stability performance is not outstanding.
[0006] Patent CN 110117143 B discloses a method for solidifying mud with magnesium-based composite materials. The method uses magnesium oxide, magnesium chloride hexahydrate, slag or slag composition, carbide slag, silicon powder, anhydrous sodium sulfate, and water-absorbent resin as raw materials. However, the method does not address the defect of poor water stability of magnesium oxychloride solidification.
[0007] Patent CN117623652A discloses a modified magnesium oxychloride cement dredged sludge solidifying agent and a preparation method thereof. The main components of the solidifying agent are magnesium oxychloride cement, sodium silicate, silica fume, and solid sulfur ash. Under the condition of 20% addition, the 7d strength of the solidified sludge is 1.1 MPa, which is relatively low.
[0008] Patent CN113735550A discloses a magnesium oxychloride cement-based slag unburned building material and a preparation method thereof. The method uses construction slag, light-burned magnesium oxide, magnesium chloride, industrial waste slag, fiber, modifier, and activator as main raw materials. The softening coefficient of the solidified material in this method is 0.83-0.91, and there is still a lot of room for improvement in water stability.
[0009] Patent CN113912373B discloses a high-performance curing agent for rapidly curing high-water content soft soil into roadbed filler. The raw materials include metakaolin, magnesium oxide, magnesium chloride, sodium silicate, sodium bicarbonate, sodium polyacrylate, sulfated castor oil, aluminum oxide, ferric chloride, aluminum chloride, and silica fume. The method uses the produced geopolymer to encapsulate the phase product of magnesium oxychloride cement, thereby improving the water stability of the cured soil, and the water stability coefficient reaches 94.6. However, the patent cannot achieve the function of sealing the pore channels of the cured soil.
[0010] From the above, it can be seen that although magnesium oxychloride-based cementitious materials have high strength, they have poor water resistance and cannot be directly used for the solidification of road base materials, which seriously limits the application of magnesium oxychloride-based cementitious materials in road engineering. Summary of the invention
[0011] Purpose of the invention: The first purpose of the present invention is to provide a soil solidifier with a self-sealing function that improves the water resistance of magnesium oxychloride-based cementitious materials; the second purpose of the present invention is to provide a method for preparing the soil solidifier with a self-sealing function.
[0012] Technical solution: The soil solidifier with pore self-sealing function of the present invention comprises the following raw materials by weight: 35-45 parts of magnesium oxide, 15-25 parts of magnesium chloride, 4-6 parts of sodium aluminate, 4-6 parts of nano-silicon dioxide, 3-5 parts of sodium silicate, 1-3 parts of gypsum, 1-3 parts of calcium chloride, 1-2 parts of polyanionic cellulose, and 2-3 parts of self-sealing functional microcapsules; wherein the self-sealing functional microcapsules comprise an outer shell and an inner core, the outer shell raw materials comprise polyvinyl alcohol, 50 parts of dimethyl sulfoxide, 3 parts of chitosan, 50 parts of formic acid, ethyl acetate, polyethylene glycol, ethanol, liquid paraffin, sorbitan oleate, glutaraldehyde solution and isopropanol, and the inner core comprises urea and urease.
[0013] Preferably, the sodium silicate is a powder with a modulus of 1.
[0014] Preferably, the magnesium oxide is light-burned magnesium oxide, and the active magnesium oxide content is not less than 65%.
[0015] Preferably, the particle size of the nano-silicon dioxide is 20-50 nm.
[0016] Preferably, in the self-enclosed functional microcapsule, the shell includes 4-6 parts of polyvinyl alcohol, 45-55 parts of dimethyl sulfoxide, 2-4 parts of chitosan, 47-53 parts of formic acid, 4-6 parts of ethyl acetate, 18-22 parts of polyethylene glycol, 15-25 parts of ethanol, 220-280 parts of liquid paraffin, 1.5-2.5 parts of sorbitan oleate, 0.8-1.2 parts of glutaraldehyde solution, and 2-3 parts of isopropanol, and the core includes 1-3 parts of urea and 0.25-0.75 parts of urease.
[0017] The preparation of microcapsules is generally carried out in an emulsion. In the present invention, in order to prepare the mixture of urease and urea into microcapsules, if the microcapsules are prepared in an aqueous solution, then during the preparation of the microcapsules, urea and water will be decomposed into carbon dioxide and ammonium radicals under the action of urease. Therefore, the preparation of microcapsules cannot be carried out in an aqueous solution, so many organic substances are selected as solvents to replace the role of water. The role of each component is as follows:
[0018] Polyvinyl alcohol is a wall material, which is mainly used to wrap the core material after the cross-linking reaction occurs.
[0019] Dimethyl sulfoxide is an organic solvent used to dissolve polyvinyl alcohol.
[0020] Chitosan is a wall material that wraps the core material and is an essential material for making the microcapsules insoluble under alkaline conditions and soluble under neutral conditions.
[0021] Formic acid is a solvent used to dissolve chitosan.
[0022] Ethyl acetate is used to adjust the viscosity of the solution and improve the subsequent emulsification effect.
[0023] Polyethylene glycol is used to coat the core material to prevent the urea and urease core materials from coming into contact with water and reacting when preparing microcapsules.
[0024] Ethanol is used as a solvent to dissolve polyethylene glycol.
[0025] Liquid paraffin is used to form an emulsion after mixing with the wall material solution.
[0026] Sorbitan oleate is used to stabilize the emulsion.
[0027] Glutaraldehyde is a cross-linking agent used to undergo a cross-linking reaction with the wall material.
[0028] Isopropyl alcohol is a neutralizing agent used to stop the cross-linking reaction.
[0029] Preferably, the urease activity is 100-200 U / mg.
[0030] Preferably, the molecular weight of the polyvinyl alcohol is 20,000-50,000, and the alcoholysis degree is 85%-90%.
[0031] Preferably, the molecular weight of the polyethylene glycol is 4000-6000.
[0032] Preferably, the deacetylation degree of the chitosan is 85-95%.
[0033] Preferably, the particle size of the urea is 1-10 um.
[0034] Preferably, the concentration of the glutaraldehyde solution is 0.8-1.2 wt %.
[0035] The ethanol is anhydrous ethanol.
[0036] The method for preparing the soil solidifying agent with pore self-sealing function of the present invention is characterized by comprising the following steps:
[0037] (1) Weigh the following raw materials according to weight: magnesium oxide, sodium aluminate, sodium silicate, polyanionic cellulose, and calcium chloride, and mix them evenly to obtain material A;
[0038] (2) Weigh the following raw materials according to weight: magnesium chloride, nano-silicon dioxide, and gypsum, and mix them evenly to obtain material B;
[0039] (3) Add material A to material B and mix well to obtain material C;
[0040] (4) Add the self-sealing functional microcapsules to material C and mix them evenly to obtain the soil solidifying agent.
[0041] Preferably, the method for preparing the self-enclosed functional microcapsules comprises the following steps:
[0042] (1) adding polyvinyl alcohol to dimethyl sulfoxide, heating and stirring to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution, and then cooling the solution to room temperature;
[0043] (2) adding chitosan to formic acid, stirring until the chitosan is completely dissolved to form a transparent solution, and adding ethyl acetate to obtain a chitosan solution;
[0044] (3) mixing the polyvinyl alcohol solution and the chitosan solution, and stirring them uniformly to form a wall material mixed solution;
[0045] (4) mixing urea and urease evenly to form a microcapsule core material mixture;
[0046] (5) adding polyethylene glycol to an ethanol solvent, heating and stirring until the polyethylene glycol is completely dissolved, to obtain a polyethylene glycol solution;
[0047] (6) adding the core material mixture of step (4) to the polyethylene glycol solution of step (5), stirring to make the polyethylene glycol evenly distributed on the surface of the core material particles, removing the solvent, and finally drying to obtain the core material particles;
[0048] (7) adding sorbitan oleate to liquid paraffin, stirring until completely dissolved, then adding the wall material mixed solution of step (3), and simultaneously adding the core material particles prepared in step (6), and then emulsifying to obtain an emulsion;
[0049] (8) adding glutaraldehyde solution to the emulsion obtained in step (7), mixing evenly, and then cross-linking polyvinyl alcohol and chitosan; then adding isopropanol solution and mixing evenly, and then separating microcapsules, and finally drying to obtain the microcapsules with pore self-sealing function.
[0050] Preferably, in step (1), the stirring heating temperature is 80° C. and the stirring time is 1 h.
[0051] Preferably, in step (5), polyethylene glycol is added to an ethanol solvent and heated to 30-40° C., and stirred until the polyethylene glycol is completely dissolved to form a uniform solution.
[0052] Preferably, in step (6), the polyethylene glycol is evenly distributed on the surface of the core material by ultrasonic stirring; the solvent is removed by placing the mixed solution in a rotary evaporator and volatilizing the solvent at 40°C; the drying temperature is 30-40°C. The drying temperature will affect the activity of urease, so the temperature must be appropriate. Too high a temperature will destroy the activity of urease.
[0053] Preferably, in step (7), the emulsification is performed using a high-speed stirrer at a speed of 3000-5000 rpm for 5-10 min.
[0054] Preferably, in step (8), the temperature of the cross-linking reaction is 25-30° C., and the reaction time is 2-4 hours. The temperature of the cross-linking reaction should be appropriate. Too high a temperature will destroy the activity of urease in the core material.
[0055] Preferably, the separation of microcapsules is: pouring the mixed solution into a centrifuge at a speed of 5000 rpm for 10-20 min to separate the microcapsules.
[0056] Invention mechanism:
[0057] When magnesium oxychloride is used as a soil solidification material to solidify soft soil, the main reaction products in the soil are 5Mg(OH)2MgCl2·8H2O (5 phases), 3Mg(OH)2MgCl2·8H2O (3 phases) and Mg(OH)2, etc. The improvement in the strength of the solidified soil is mainly contributed by the reaction products 5 phase and 3 phase. However, the reaction products 5 phase and 3 phase of magnesium oxychloride have poor water resistance and are easily hydrolyzed in water, resulting in a decrease in the strength of the solidified soil. The solidified soil will inevitably be affected by natural factors such as rainfall and rising groundwater levels during long-term service. This is also the main reason why the engineering application of magnesium oxychloride in solidified soil is limited. In order to achieve the long-term stability of magnesium oxychloride solidified soil during long-term use, the present invention has been innovated and optimized from the following aspects:
[0058] (1) When magnesium oxychloride is used to solidify soil, the water-chlorine ratio needs to be between 10 and 20 to promote the formation of phase 5 and phase 3 products. However, in general, the water-chlorine ratio when magnesium oxychloride is used to solidify soil will be higher than this suitable water-chlorine ratio range, resulting in less generation of phase 5 and phase 3 products, which reduces the strength of the solidified soil. Polyanionic cellulose has a strong water absorption capacity and can absorb free water in the soil, which has the function of reducing the water-chlorine ratio in the solidified soil. In addition, polyanionic cellulose can form an emulsion after absorbing water, blocking the pore channels of free water entering the solidified soil, thereby improving the water resistance of the soil solidified by magnesium oxychloride.
[0059] (2) The microcapsules designed in the present invention are insoluble under alkaline conditions but soluble under neutral conditions. When magnesium oxychloride is used to solidify soil, the free water in the soil is alkaline in the early stage of the reaction. The wall material of the microcapsule remains stable in the alkaline aqueous solution and does not dissolve, and the active substances in the microcapsule do not react. During the long-term service of the solidified soil, affected by factors such as rainfall, external water will enter the solidified soil through the pore channels of the solidified soil. At this time, the pH value of the free water in the pores of the soil body decreases, the wall material of the microcapsule dissolves, and urea and urease are released. Urea and free water in the pores generate carbon dioxide and ammonia under the catalysis of urease. Carbon dioxide reacts with magnesium hydroxide, the reaction product of magnesium oxychloride, and phase 5 and phase 3 to generate reaction products such as magnesite, calcite and hydrocarbide with cementing and swelling effects. At the same time, in this reaction process, a large amount of free water in the pores will be consumed. These reaction products can improve the strength of the solidified soil, and can also wrap the phase 5 and phase 3, cut off the contact between the phase 5 and phase 3 and the pore water, and improve the water stability of the magnesium oxychloride reaction products (phase 5 and phase 3). At the same time, because magnesite, calcite and hydrocarbide are expansive, they can block the pore channels of external water entering the solidified soil, making it difficult for external water to enter the solidified soil, further improving the water stability of the solidified soil. At the same time, since the expansive products can fill the pores, the interior of the solidified soil is further compacted, thereby improving the strength of the solidified soil.
[0060] (3) When the molar ratio of magnesium oxide to magnesium chloride is between 5 and 8, more 5-phase products are generated, which is more beneficial to the improvement of the strength of the solidified soil. Sodium aluminate reacts with magnesium chloride to generate magnesium hydroxide, which increases the molar ratio of magnesium oxide to magnesium chloride, so that the molar ratio of magnesium oxide to magnesium chloride in the present invention is in the range of 5-8, which promotes the improvement of the strength of the solidified soil. When the wall material is dissolved, urea is hydrolyzed under the action of urease to produce ammonium ions, so that the pH value of the pore water is between 11 and 12. Under alkaline conditions, sulfate ions, calcium ions, aluminate ions and silicate ions, nano-silicon dioxide, etc. react to generate calcium sulfoaluminate substances, which compact the soil and can cover and encapsulate the 5-phase and 3-phase products, further improving the strength and water stability.
[0061] Based on the above technical principles, the solidified soil can be made to have a self-sealing pore function, which makes the solidified soil have excellent water stability and durability.
[0062] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The curing agent introduces sodium aluminate, nano-silicon dioxide, sodium silicate, gypsum, calcium chloride, polyanionic cellulose and self-sealing functional microcapsules on the basis of magnesium oxychloride curing material, thereby improving the water resistance of magnesium oxychloride-based gelling material; (2) The solidified soil after being cured by the curing agent has high strength and good water resistance, and its 7d unconfined compressive strength can reach more than 3MPa, and its water stability coefficient can reach more than 100%, which can meet the needs of road base soil curing. In addition, the production process of magnesium oxychloride has low energy consumption and low carbon emissions, and has significant social and economic benefits. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further described below in conjunction with embodiments.
[0064] The soil solidifying agent with pore self-sealing function of the present invention comprises raw materials including:
[0065] Magnesium oxide: 35-45 parts;
[0066] Magnesium chloride: 15-25 parts;
[0067] Sodium aluminate: 4-6 parts;
[0068] Nano silicon dioxide: 4-6 parts;
[0069] Sodium silicate: 3-5 parts;
[0070] Gypsum: 1-3 parts;
[0071] Calcium chloride: 1-3 parts;
[0072] Polyanionic cellulose: 1-2 parts;
[0073] Self-sealed functional microcapsules: 2-3 parts.
[0074] The raw materials selected in Examples 1-3 were implemented according to the proportions in Table 1, with a total of 3 groups of examples.
[0075] Table 1 Raw material ratios of Examples 1 to 3 (parts by mass)
[0076]
[0077] Wherein, sodium silicate is powder with a modulus of 1; magnesium oxide is light-burned magnesium oxide; and the particle size of nano silicon dioxide is 20-50 nm.
[0078] The self-enclosed functional microcapsule comprises raw materials: 5 parts of polyvinyl alcohol, 50 parts of dimethyl sulfoxide, 3 parts of chitosan, 50 parts of formic acid, 5 parts of ethyl acetate, 2 parts of urea, 0.5 parts of urease, 20 parts of polyethylene glycol, 20 parts of ethanol, 250 parts of liquid paraffin, 2 parts of sorbitan oleate, 1 part of glutaraldehyde solution, and 2.5 parts of isopropanol; wherein the molecular weight of the polyvinyl alcohol is 20000-50000, and the alcoholysis degree is 88%; the deacetylation degree of the chitosan is 85-95%; the particle size of the urea is 1-10um; the urease activity is 140U / mg; the molecular weight of the polyethylene glycol is 4000-6000; the concentration of the glutaraldehyde solution is 1wt%; and the preparation method comprises the following steps:
[0079] (1) adding polyvinyl alcohol to dimethyl sulfoxide, stirring and heating to 80° C. for about 1 hour to form a uniform transparent solution, dissolving the polyvinyl alcohol completely, and then cooling the solution to room temperature;
[0080] (2) adding chitosan to formic acid, stirring until the chitosan is completely dissolved to form a transparent solution, and then adding ethyl acetate;
[0081] (3) mixing the polyvinyl alcohol solution and the chitosan solution, and stirring them uniformly to form a mixed solution of the wall material;
[0082] (4) mixing urea and urease, ensuring uniform stirring and avoiding direct contact with moisture in the air, to form a microcapsule core material mixture;
[0083] (5) Add polyethylene glycol to the ethanol solvent, heat to 35° C. and stir until the polyethylene glycol is completely dissolved to form a uniform solution;
[0084] (6) slowly adding the core material mixture into the polyethylene glycol solution, and using ultrasonic stirring to make the polyethylene glycol evenly distributed on the surface of the core material particles;
[0085] (7) placing the mixed solution obtained in step (6) in a rotary evaporator to evaporate the solvent at 40° C.;
[0086] (8) placing the core material particles obtained in step (7) in a drying oven and drying at 35° C.;
[0087] (9) Add sorbitan oleate to liquid paraffin and stir with ultrasonic until completely dissolved;
[0088] (10) slowly adding the wall material mixed solution to the solution in step (9), and simultaneously adding the core material particles, and emulsifying using a high-speed stirrer at a speed of 4000 rpm for 8 minutes to ensure uniform mixing;
[0089] (11) Slowly adding the glutaraldehyde solution to the emulsion obtained in step (10) at a stirring speed of 350 rpm for 3 hours at a temperature of 27° C.;
[0090] (12) Add isopropanol solution to the solution obtained in the previous step, stir at a speed of 250 rpm, and stir for 30 min;
[0091] (13) Pour the solution obtained in the previous step into a centrifuge at a speed of 5000 rpm for 15 min to separate the microcapsules.
[0092] (14) The microcapsules were placed in a drying oven and dried at 35 °C for 10 h to prepare microcapsules with pore self-sealing function.
[0093] The preparation method of the soil solidifying agent with pore self-sealing function comprises the following steps:
[0094] During the implementation process, the raw materials were accurately weighed according to the proportions shown in Table 1. First, magnesium oxide, sodium aluminate, sodium silicate, polyanionic cellulose, and calcium chloride were mixed and ultrasonically stirred for 20 minutes to obtain material A. Then, magnesium chloride, nano-silicon dioxide, and gypsum were mixed and uniformly stirred for 20 minutes to obtain material B. Subsequently, material A was added to material B, mixed uniformly and stirred for 8 minutes to obtain material C. Finally, self-enclosed functional microcapsules were added to material C, mixed uniformly and stirred for 20 minutes to obtain the material of the present invention.
[0095] The solidified materials in Examples 1 to 3 were mixed with soft soil with a moisture content of 17% in a weight ratio of 9:100, stirred evenly, poured into a three-petal saturator, and made into a cylindrical sample with a diameter of (50 mm) × height of (50 mm) and a compaction degree of 97%. The cylindrical sample was placed in a standard curing box for curing (temperature 20±1°C, relative humidity ≥95%) and cured to the corresponding age. According to the Highway Geotechnical Test Code (JTG 3430-2020), the compressive strength of the sample was measured. The test results are shown in Table 1:
[0096] Table 2 Compressive strength and water stability coefficient test results of Examples 1-3
[0097]
[0098] The test results show that the three curing agents prepared with the three mix ratios given in the embodiment have a good curing effect on soft soil, and the unconfined compressive strength of the normal curing for 7 days exceeds 3.51MPa, and the highest can reach 3.93MPa; because the curing material contains microcapsules with pore self-sealing function, the reaction product can further improve the strength of the sample, so the unconfined compressive strength of the sample after normal curing for 6 days and then soaking in water for 1 day is further increased. In Example 1, the strength increases from 3.51MPa to 4.36MPa, and in Example 3, the strength increases from 3.93MPa to 5.26MPa. The water stability coefficients of the three groups of embodiments all exceed 100%, and the highest can reach 133.8%. At the same time, the water absorption of the three groups of samples is only 3.11g at most, indicating that the curing material has excellent water stability. Therefore, the curing material disclosed in the present invention has high strength and water stability, and can meet the use requirements of road base curing soil.
[0099] Embodiment 4-5
[0100] On the basis of Example 1, the self-enclosed functional microcapsules are changed as shown in Table 3, and the other conditions are the same as Example 1. According to the Highway Geotechnical Test Code (JTG 3430-2020), the compressive strength of the sample is measured, and the test results are shown in Table 4:
[0101] Table 3 Raw material ratios of Examples 4 to 5 (parts by mass)
[0102]
[0103]
[0104] Table 4 Compressive strength and water stability coefficient test results of comparative example 1
[0105]
[0106] The test results show that:
[0107] The three mix ratios of curing agents given in Examples 4-5 have good curing effects on soft soil, and the unconfined compressive strength after 7 days of normal curing exceeds 3.41 MPa. Since the curing material contains microcapsules with pore self-sealing function, the reaction product can further improve the strength of the sample. Therefore, the unconfined compressive strength of the sample is further increased after 6 days of normal curing and then soaking in water for 1 day. In Examples 4-5, the strength exceeds 4 MPa. The water stability coefficients of the two groups of embodiments exceed 100%, and can reach up to 124.5%. At the same time, the maximum water absorption of the two groups of samples is only 3.08 g, indicating that the curing material has excellent water stability.
[0108] Comparative Example 1
[0109] The raw materials of this comparative example include: 40 parts of magnesium oxide and 20 parts of magnesium chloride. The selected raw materials are the same as those of Examples 1-3.
[0110] Preparation method: Mix magnesium oxide and magnesium chloride and stir evenly for 10 minutes to obtain the material described in Comparative Example 1.
[0111] According to the Highway Geotechnical Test Code (JTG 3430-2020), the compressive strength of the sample was measured. The test results are shown in Table 5:
[0112] Table 5 Comparative Example 1 Compressive strength and water stability coefficient test results
[0113]
[0114] The test results show that the unconfined compressive strength of the solidified material shown in Comparative Example 1 is lower than that in Example 2, the water stability coefficient is sharply reduced, and the water absorption is also sharply increased, which cannot meet the requirements of soil solidification.
[0115] Comparative Example 2
[0116] The raw materials for this comparative example include:
[0117] 40 parts of magnesium oxide, 20 parts of magnesium chloride, 1.5 parts of polyanionic cellulose, the selected raw materials are the same as those in Example 1-3.
[0118] Preparation method: First, magnesium oxide and polyanionic cellulose were mixed and ultrasonically stirred for 20 minutes to obtain material A. Then, material A was added with magnesium chloride, mixed evenly and stirred for 8 minutes to obtain the material described in comparative example 2.
[0119] According to the Highway Geotechnical Test Code (JTG 3430-2020), the compressive strength of the sample was measured. The test results are shown in Table 6:
[0120] Table 6 Compressive strength and water stability coefficient test results of comparative example 2
[0121]
[0122] The test results show that the compressive strength of the solidified material shown in Comparative Example 2 is sharply reduced. In addition, the water stability coefficient in Comparative Example 2 is reduced compared with that in the embodiment, and the water absorption is also sharply increased, so it cannot meet the use requirements of soil solidification materials. Although polyanionic cellulose is added to Comparative Example 2, the molar ratio of magnesium oxide and magnesium chloride is not in the range suitable for generating 5-phase products, so the 7d unconfined compressive strength is sharply reduced. In addition, since microcapsules with self-sealed pores are not added, after the sample is soaked in water, the 5-phase product is hydrolyzed, and the cementation structure inside the sample is destroyed, resulting in a sharp reduction in the water stability coefficient.
[0123] Comparative Example 3
[0124] The raw materials of this comparative example include: 40 parts of magnesium oxide, 20 parts of magnesium chloride, 5 parts of sodium aluminate, 5 parts of nano silicon dioxide, 4 parts of sodium silicate, 2 parts of gypsum, and 2 parts of calcium chloride. The selected raw materials are the same as those in Examples 1-3.
[0125] Preparation method: First, magnesium oxide, sodium aluminate, sodium silicate, and calcium chloride are mixed and ultrasonically stirred for 20 minutes to obtain material A. Then, magnesium chloride, nano-silicon dioxide, and gypsum are mixed and uniformly stirred for 20 minutes to obtain material B. Finally, material A is added to material B, mixed uniformly and stirred for 8 minutes to obtain the material described in comparative example 3. According to the Highway Geotechnical Test Code (JTG3430-2020), the compressive strength of the sample is measured, and the test results are shown in Table 7:
[0126] Table 7 Compressive strength and water stability coefficient test results of comparative example 3
[0127]
[0128] The test results show that the unconfined compressive strength of the cured material shown in Comparative Example 3 is significantly lower than that in Example 2, and the water stability coefficient is also significantly lower than that in Example 2, and the increase in water absorption is also significant. This is because in this comparative example, although the molar ratio of magnesium oxide and magnesium chloride enters the range suitable for the generation of five-phase products, the water-chlorine ratio is too high due to the lack of the addition of polyanionic cellulose and self-sealing functional microcapsules, which affects the growth of the sample strength. In addition, due to the lack of the addition of microcapsules, the water stability is also sharply reduced.
[0129] Comparative Example 4
[0130] The raw materials of this comparative example include: 40 parts of magnesium oxide, 20 parts of magnesium chloride, 5 parts of sodium aluminate, 5 parts of nano-silicon dioxide, 4 parts of sodium silicate, 2 parts of gypsum, 2 parts of calcium chloride, and 1.5 parts of polyanionic cellulose. The selected raw materials are the same as those in Examples 1-3.
[0131] Preparation method: First, magnesium oxide, sodium aluminate, sodium silicate, polyanionic cellulose, and calcium chloride were mixed and ultrasonically stirred for 20 minutes to obtain material A. Subsequently, magnesium chloride, nano-silicon dioxide, and gypsum were mixed and uniformly stirred for 20 minutes to obtain material B. Finally, material A was added to material B, mixed uniformly and stirred for 8 minutes to obtain the material described in comparative example 4.
[0132] According to the Highway Geotechnical Test Code (JTG 3430-2020), the compressive strength of the sample was measured. The test results are shown in Table 8:
[0133] Table 8 Compressive strength and water stability coefficient test results of comparative example 4
[0134]
[0135] The test results show that the unconfined compressive strength of Comparative Example 4 after 7 days of standard curing is basically close to that of Example 2, but the strength decreases significantly after 6 days of standard curing and 1 day of soaking in water, and the water stability coefficient is also much different from that of the example, and the water absorption also increases sharply, which does not meet the requirements of soil solidification. This is because the self-sealing functional microcapsules were not added in the comparative example, resulting in the hydrolysis of the 5-phase product after the sample was soaked in water, so the water stability coefficient of the sample decreased sharply.
[0136] Comparative Example 5
[0137] The raw materials of this comparative example include: 40 parts of magnesium oxide, 20 parts of magnesium chloride, 2 parts of gypsum, 1.5 parts of polyanionic cellulose, and 2.5 parts of self-sealing functional microcapsules. The selected raw materials are the same as those of Examples 1-3.
[0138] Preparation method: First, magnesium oxide and polyanionic cellulose are mixed and ultrasonically stirred for 20 minutes to obtain material A. Secondly, magnesium chloride and gypsum are mixed and uniformly stirred for 20 minutes to obtain material B. Subsequently, material A is added to material B, mixed uniformly and stirred for 8 minutes to obtain material C. Finally, self-enclosed functional microcapsules are added to material C, mixed uniformly and stirred for 20 minutes to obtain the material of the present invention.
[0139] According to the Highway Geotechnical Test Code (JTG 3430-2020), the compressive strength of the sample was measured. The test results are shown in Table 9:
[0140] Table 9 Compressive strength and water stability coefficient test results of comparative example 5
[0141]
[0142] The test results show that although the water stability coefficient in comparative example 5 is close to that in example 2, the unconfined compressive strength after standard curing for 7 days and the unconfined compressive strength after soaking in water are significantly reduced compared with those in the example. This is because sodium aluminate, nano-silicon dioxide, sodium silicate and calcium chloride are not added in the comparative example, so that the molar ratio of magnesium oxide and magnesium chloride is lower than the range suitable for the generation of five-phase products, and the five-phase reaction products that directly contribute to the strength of the sample are insufficient, resulting in a significant deterioration in the strength of the sample. However, due to the addition of microcapsules, the strength of the sample increases after soaking in water.
Claims
1. A soil solidifying agent with pore self-sealing function, characterized in that: By weight, it includes the following raw materials: The invention comprises 35-45 parts of magnesium oxide, 15-25 parts of magnesium chloride, 4-6 parts of sodium aluminate, 4-6 parts of nano silicon dioxide, 3-5 parts of sodium silicate, 1-3 parts of gypsum, 1-3 parts of calcium chloride, 1-2 parts of polyanionic cellulose and 2-3 parts of self-sealed functional microcapsules; wherein the self-sealed functional microcapsules comprise an outer shell and an inner core, the outer shell raw materials comprise polyvinyl alcohol, 50 parts of dimethyl sulfoxide, 3 parts of chitosan, 50 parts of formic acid, ethyl acetate, polyethylene glycol, ethanol, liquid paraffin, sorbitan oleate, glutaraldehyde solution and isopropanol, and the inner core comprises urea and urease.
2. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: In the self-enclosed functional microcapsule, the outer shell comprises 4-6 parts of polyvinyl alcohol, 45-55 parts of dimethyl sulfoxide, 2-4 parts of chitosan, 47-53 parts of formic acid, 4-6 parts of ethyl acetate, 18-22 parts of polyethylene glycol, 15-25 parts of ethanol, 220-280 parts of liquid paraffin, 1.5-2.5 parts of sorbitan oleate, 0.8-1.2 parts of glutaraldehyde solution, and 2-3 parts of isopropanol, and the inner core comprises 1-3 parts of urea and 0.25-0.75 parts of urease.
3. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: The urease activity is 100-20 U / mg.
4. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: The molecular weight of the polyvinyl alcohol is 20,000-50,000.
5. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 4000-6000.
6. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: The deacetylation degree of the chitosan is 85-95%.
7. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: The particle size of the urea is 1-10 um.
8. The soil solidifying agent with pore self-sealing function according to claim 1, characterized in that: The concentration of the glutaraldehyde solution is 0.8-1.2 wt %.
9. A method for preparing a soil solidifying agent with pore self-sealing function according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh the following raw materials according to weight: magnesium oxide, sodium aluminate, sodium silicate, polyanionic cellulose, and calcium chloride, and mix them evenly to obtain material A; (2) Weigh the following raw materials according to weight: magnesium chloride, nano-silicon dioxide, and gypsum, and mix them evenly to obtain material B; (3) Add material A to material B and mix well to obtain material C; (4) Add the self-sealing functional microcapsules to material C and mix them evenly to obtain the soil solidifying agent.
10. The method for preparing a soil solidifying agent with pore self-sealing function according to claim 9, characterized in that: The preparation of the self-enclosed functional microcapsules comprises the following steps: (1) adding polyvinyl alcohol to dimethyl sulfoxide, heating and stirring to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution, and then cooling the solution to room temperature; (2) adding chitosan to formic acid, stirring until the chitosan is completely dissolved to form a transparent solution, and adding ethyl acetate to obtain a chitosan solution; (3) mixing the polyvinyl alcohol solution and the chitosan solution, and stirring them uniformly to form a wall material mixed solution; (4) mixing urea and urease evenly to form a microcapsule core material mixture; (5) adding polyethylene glycol to an ethanol solvent, heating and stirring until the polyethylene glycol is completely dissolved, to obtain a polyethylene glycol solution; (6) adding the core material mixture of step (4) to the polyethylene glycol solution of step (5), stirring to make the polyethylene glycol evenly distributed on the surface of the core material particles, removing the solvent, and finally drying to obtain the core material particles; (7) adding sorbitan oleate to liquid paraffin, stirring until completely dissolved, then adding the wall material mixed solution of step (3), and simultaneously adding the core material particles prepared in step (6), and then emulsifying to obtain an emulsion; (8) adding glutaraldehyde solution to the emulsion obtained in step (7), mixing evenly, and then cross-linking polyvinyl alcohol and chitosan; then adding isopropanol solution and mixing evenly, and then separating microcapsules, and finally drying to obtain the microcapsules with pore self-sealing function.
Citation Information
Patent Citations
Magnesium oxysulfate-based raw soil curing agent as well as preparation method and application thereof
CN109305794A
A method for curing magnesium-based composite material slurry
CN110117143B
Magnesium oxychloride cement-based muck baking-free building material and preparation method thereof
CN113735550A
A high-performance curing agent for rapid solidification of soft soil with high water content into roadbed fill material.
CN113912373B
Cited By
Pavement composite soil stabilizer as well as preparation method and application thereof
CN121379611A